Rancang Bangun Heat Exchanger Tube Non Fin Tiga Pass, Shell Satu Pass Untuk Mesin Pengering Empon-Empon - Alfan Ghozali, Farug, Sartono Putro, Ir. MT (2017)
Heat Exchanger is the equipment used to perform the process the exchange of heat between two fluids, liquid (hot or cold) and gas, where the fluid has different temperatures. This study intend to determine the heat transfer with debit variation 0,026, 0,028 and 0,030 m^3/s. Heat exchangers are used in this research has a cross flow. The heat exchangers mecanism are cold fluid in form of air obtained from the blower to flow into the heat exchanger, in this process cold fluid will receive heat from hot fluid coming from the stove, and the cold fluid flows into the engine drying machine medicinal. The result of this research show that, if the cold fluid mass flow rate of air are bigger, it is means that temperature different, heat of cold fluid mass flow, ,overall heat transfer coefficient,heat transfer coefficient of cold fluid, efficiency and mass different of turmeric rate is bigger.